Análise dos modelos de remuneração médica no setor de saúde suplementar brasileiro - Bessa, Ricardo de Oliveira (2011)
Because of technological advances and increased average life expectancy of the population, among other factors, spending on health care has grown significantly in Brazil. On one hand, health medical operators readjust their values to cope with increased costs, leading to complaints from its contractors and beneficiaries about rising prices. On the other hand, the medical service providers seem dissatisfied with their remunerations. Therefore, an impasse, which has been little studied and this work seeks to address, arises. Based on an extensive literature research and on interviews with executives and leaders in the field of health care, first presented are the profile of the sector and the major medical payment models in the country. Subsequently, the research results are discussed, giving voice to representatives of health medical operators and the medical profession. Among the main findings of the qualitative research are: the predominance of payment models by procedure or fee for service; widespread criticism about the emphasis that the fee for service model puts on quantity, not quality; the expectation that models capable of evaluating the performance of doctors and health care outcomes will be developed. The development of this new model would bring several benefits, not only economic, as long as the construction of performance and quality indicators can be decided with the participation of all stakeholders, including physicians. Only then we will come to a payment model that reduces unnecessary procedures (and costs), prioritize service quality, optimize the results and improve the satisfaction of everyone involved in health care.